Retention of knowledge after basic life support course for professional football coaches: A prospective study - Yazla, Merve; Şafak, Tuba; Koçak, Abdullah Osman; Katipoglu, Burak (The European Research Journal, 2025)
Objectives: Teaching more people high-quality CPR through more efficient training methods can improve the rates and quality of Cardiopulmonary resuscitation (CPR) in cases of out-of-hospital cardiac arrest and help save more lives. In this study, we aimed to provide online Basic Life Support (BLS) training to football coaches who are in close contact with the risk group, and to examine the effectiveness of the training, to what extent they retained basic life support knowledge after completing the training program, and to determine the time of booster training. Methods: Online BLS training was provided to football coaches. Pre- and post-tests were administered to measure the effectiveness of online BLS training. A retention test was administered to one group after 3 months and to one group after 6 months to evaluate the permanence of the training. Results: Knowledge gain was significant immediately after the BLS course. There was no difference between the two groups in the post-training test results. Overall level of knowledge decreased significantly after three and six months. While there was a 5-point decrease in the retention test performed after three months, a 12-point reduction after six months. Conclusions: There is no clear answer yet regarding the time and frequency of booster training. Rather than single training, the most effective approach will be to integrate booster content with short training videos at intervals of 3-6 months. Online BLS training videos can serve as an alternative.